Strategic planning in healthcare sector for sustainable and medical quality performance - Ali, Albadri Albaloula (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to identify the strategic planning (SP) issues that the healthcare sector faces, identify the most effective strategic management (SM) methods to address these issues, and propose a framework that can adjust to the industry's complexity and constant change. The methodology employed involves using the study's title or related subject matter; the author has chosen a total of 22 pertinent research articles from reputable electronic databases and academic peer-reviewed open access journals. The study found that dynamic change, complexity, interconnection, and unpredictable factors in the healthcare context have been identified. SM and SP have been proven to be the most appropriate management methods for addressing healthcare challenges. Various SM and SP methods and frameworks have been found and used in healthcare sectors. Transformational and strategic leaders in healthcare play significant roles in effectively leading the healthcare sector, especially during crises and pandemic situations. The reviewed studies and literature are from and about the healthcare industry, and their goals and focus are on SP domains, which sets this study apart. The study concludes by emphasizing the importance of SP/SM in the healthcare sector, as well as its practical implications for setting high sustainable healthcare quality.